Gains vs losses in pay-for-performance: Stated preference evidence from a U.S. survey - Justin G. Trogdon; Aveena Khanderia; Kathryn Brignole; Jodi A. Lewis; Tara Licciardello Queen (PLoS ONE, 2025)
Background Pay-for-performance (P4P) incentives can be paid as a bonus (gain) or a penalty (loss). Diminishing marginal utility of wealth suggests that, starting from the same initial wealth, individuals dislike losses more than they like equivalent gains. Objective This study reports the minimum financial gain or loss required to motivate primary care providers and clinical staff to try to increase their human papillomavirus (HPV) vaccination rates. Data In 2022, we conducted a national U.S. survey through WebMD’s Medscape Network of clinical staff working in primary care clinics that provided HPV vaccination to children ages 9 through 12 years (N = 2,527; response rate = 57%). Methods We randomized respondents to one of two hypothetical HPV vaccine incentive designs: a bonus for reaching an unspecified target HPV vaccination rate and a penalty for failing to reach the unspecified target. The primary outcome is the self-reported smallest incentive amount (U.S. dollars) that would motivate participants to try and increase their HPV vaccination rates. We tested for differences across P4P designs using unadjusted responses and linear regressions adjusting for clinic and respondent characteristics. We also tested for heterogeneous responses by experience with incentizves, training, and rurality. Results The mean amount required to motivate effort was $2,155 in the gain P4P design and $1,185 in the loss P4P design (unadjusted difference =  $970 [p < 0.001], adjusted difference =  $967 [p < 0.001]). There were no heterogeneous effects by rurality or experience with incentives. Physicians reported the highest differences (in dollars) between gain and loss P4P designs. Conclusions Stated preference data from primary care clinical staff suggests that effective P4P incentives could be half as large if designed as losses rather than gains.